Tinjauan Implementasi Media Audio Visual Dalam Pembelajaran Senam Lantai Rolling Depan Di SMP Negeri 15 Padang - Dina Junita; Sri Gusti Handayani; Zulbahri; Riand Resmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research problem stems from students' low interest, motivation, and understanding of forward rolling, and the need for more engaging, effective, and easily understood learning innovations. Conventional learning often leads to students' inactivity and lack of enthusiasm in participating in the learning process. This study aimed to determine the implementation of audio-visual media in forward rolling floor gymnastics lessons at SMP Negeri 15 Padang. The study used a descriptive method, with a population of 643 students at SMP Negeri 15 Padang. A sample of 34 students was selected using purposive random sampling. The instrument used was a closed-ended questionnaire with a Guttman scale consisting of 40 questions and covering ten indicators of audio-visual media implementation. Data were analyzed using frequency distribution techniques and presented in percentages. The results showed that the implementation of audio-visual media in forward rolling floor gymnastics lessons was categorized as very good. The use of audio-visual media increased students' attention, motivation, and understanding of the material being taught. Furthermore, these media help students understand the stages of movement more clearly, increase engagement during learning, strengthen memory, and support the creation of a more effective, engaging, enjoyable, and meaningful learning process for students in various learning situations at school in an optimal and sustainable manner.